Screening Wild Birds for Tick-Borne Zoonotic Pathogens in Portugal - Filipa Loureiro; João R. Mesquita; Luís Cardoso; Sérgio Santos-Silva; Guilherme Moreira; Jaqueline T. Bento; Vanessa Soeiro; Andreia Gonçalves; Filipe Silva; Patrícia F. Barradas; Ana C. Matos; Manuela Matos; et al. (Pathogens)
Wild birds may be involved in the transmission of agents of infectious diseases, including zoonoses, a circumstance which raises a number of public and animal health issues. Migratory bird species play a significant role in the introduction of tick-borne pathogens to new geographic areas, contributing to the dissemination of various etiological agents. This preliminary study aimed to assess the occurrence of four potentially zoonotic pathogens (Hepatozoon spp., Borrelia spp., Babesia spp. and Theileria spp.) in the wild birds of Portugal. Blood and tissue samples were taken from 103 birds admitted at wildlife rehabilitation centers. Through the use of conventional PCR, our findings indicate no evidence of the circulation of these pathogens among the studied bird populations in the region. In the One Health context, it is relevant to understand how faraway avian populations play a role in the epidemiology of infectious diseases. Further molecular studies are needed to deepen the knowledge of avian piroplasmosis, borreliosis and hepatozoonosis.